The influence of competence, communication and organizational culture on employee performance at office DPMP2TSP Langkat regency - Dea Okviar Egano Napitupulu; Hilman Saidi Raja Bakkol Hrp; Arham Syaukani (Trigin Publisher, 2023)
This study aims to determine the effect both collectively and partially between competency, communication and organizational culture on employee performance at the One Stop Integrated Investment and Licensing Service Office in Langkat Regency. This study uses a quantitative method with explanatory research using primary data and secondary data.The results showed that the variables of competence, communication and organizational culture together had a positive and significant effect on employee performance. This is proven by the statistical results of the regression test, which yielded a value smaller than α (α = 0.05) with a probability of 0.000. With a calculated F value > F table, namely 87.343 > 2.91, this competence can be demonstrated explain , communication and organizational culture have a positive and significant impact on employee performance. So the fourth hypothesis is accepted. The results also show a coefficient of determination (R2) of 0.88, meaning that 88.4% of the dependent variable (employee performance) is influenced or explained by the independent variables of competency, communication, and organizational culture, and the remaining 11.6% (100 % - 88.4%) influenced or explained by other variables outside of the variables used in this study